Case report: A rare progression of Necrotising Otitis Externa resulting in septic arthritis of the TMJ, a pressing matter - Daanesh Zakai; Ravir Singh Bhatti; Daya Singh Gahir; Richard Gareth Rowlands; Jooly Joseph (Elsevier, 2021)
This report outlines a multidisciplinary approach of ENT and Maxillofacial (OMFS) in the management of septic arthritis in a patient suffering with Necrotising Otitis Externa. The patient presented with persistent intermittent pain from his left ear and was diagnosed with septic arthritis of the left TMJ. The management procedure adopted was open joint wash out of the TMJ, performed in emergency theatre. The treatment proved successful and the patient was discharged on antibiotics administered via peripherally inserted central catheter (PICC).